Systemic granulomatous reaction secondary to treatment of bladder cancer with Bacillus Calmette-Guerin - Caterina Giovanna Valentini; Valentina Bozzoli; Anna Rita Larici; Luigi Maria Larocca; Giovanni Delogu; Giuseppe Leone; Livio Pagano (Mediterranean Journal of Hematology and Infectious Diseases)
Intravesical instillation of Bacillus Calmette-Guérin is the elective treatment for transitional cell and in situ bladder carcinoma. Severe complications occur very seldom, but must be known and promptly recognized. We describe the case of a 48-year-old man, treated with chemo-immunotherapy ten years before for a follicular lymphoma, who developed a systemic granulomatous reaction after his twelfth intravescical BCG instillation for bladder cancer.